Evaluation of design managers’ views of decision-making: propositions for situational awareness in building design - Lappalainen, Eelon; Seppänen, Olli; Peltokorpi, Antti; Uusitalo, Petri; Reinbold, Ana (Frontiers in Built Environment, 2025)
Building design management (BDM) is a complex, iterative, and highly collaborative process, which poses several challenges for design managers (DMRs). One challenge relates to the diversity of the information required for decision-making and the resulting limited situational awareness (SA). The construction industry has shown interest in the SA concept, although its applications have so far remained confined to construction management and production, rather than design or its management. This geographically limited study, which explores decision-making in building design management from the DMR perspective, specifically explores how situational awareness manifests in DMRs’ decision-making processes. The research data were collected through a literature review, an expert workshop, and expert interviews. The most interesting findings regarding the applicability of the situational awareness concept in BDM relate to the changing roles of the DMR, the changing balance of decision-making power, and the proposal-based decision-making practices in BDM. In this paper, we propose a novel conceptual framework for situational awareness in BDM, thereby contributing to BDM research and encouraging practitioners toward more holistic development of SA systems, including design. The framework can serve as a catalyst for future construction projects where SA systems are intended to be adopted at the design phase.